(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This text discusses how in the nineteenth century the conservative Catholic press in Chile judged the politics of the mexican president Benito Juárez. On August 25, 1872, with the news in Chile of the death of Juárez the daily El Independiente, with tendencies toward the conservative party, dedicated its editorial column to a discussion of the defeat of Mexico and the conduct of the great man in the Reform. The portrait was harsh, negating Juárez hero status or that of patriotic defender in the conception of his lack of republican virtues and tireless public ambition. But more than anything, they accused Juárez of squandering the opportunity of consolidating Mexico and its institutions after the defeat in 1867 of the Empire of the Archduke Maximiliano of Austria. In sum, Juárez was presented as a champion of “revolutionary violence” that “devastated” “Spanish America” and Europe.